Organizational influences on the use of low-value care in primary health care - a qualitative interview study with physicians in Sweden - Gabriella Lang; Sara Ingvarsson; Henna Hasson; Per Nilsen; Hanna Augustsson (Taylor & Francis Group, 2022)
AbstractAim The aim was (1) to explore organizational factors influencing the use of low-value care (LVC) as perceived by primary care physicians and (2) to explore which organizational strategies they believe are useful for reducing the use of LVC.Design Qualitative study with semi-structured focus group discussions (FGDs) analyzed using qualitative content analysis.Setting Six publicly owned primary health care centers in Stockholm.Subjects The participants were 31 primary care physicians. The number of participants in each FGD varied between 3 and 7.Main outcome measures Categories and subcategories reporting organizational factors perceived to influence the use of LVC and organizational strategies considered useful for reducing the use of LVC.Results Four types of organizational factors (resources, care processes, improvement activities, and governance) influenced the use of LVC. Resources involved time to care for patients, staff knowledge, and working tools. Care processes included work routines and the ways activities and resources were prioritized in the organization. Improvement activities involved performance measurement and improvement work to reduce LVC. Governance concerned organizational goals, higher-level decision making, and policies. Physicians suggested multiple strategies targeting these factors to reduce LVC, including increased patient-physician continuity, adjusted economic incentives, continuous professional development for physicians, and gatekeeping functions which prevent unnecessary appointments and guide patients to the appropriate point of care. .Conclusion The influence of multiple organizational factors throughout the health-care system indicates that a whole-system approach might be useful in reducing LVC.KEY POINTSWe know little about how organizational factors influence the use of low-value care (LVC) in primary health care.Physicians perceive organizational resources, care processes, improvement activities, and governance as influences on the use of LVC and LVC-reducing strategies.This study provides insights about how these factors influence LVC use.Strategies at multiple levels of the health-care system may be warranted to reduce LVC.